Breeding report of a new strawberry variety Zhongmei Huayue - ZHAO Xia; LI Gang; LIU Lifeng; SONG Yanhong; HU Panpan; ZHOU Houcheng (Guoshu xuebao)
Zhongmei Huayue is a new strawberry variety selected from a cross between Ningyu and Kaorino. The hybrid seeds were obtained by artificial hybridization pollination in February 2015 and stored at 4 ℃. The seeds were sown in May 2015, about 800 hybrid seedlings were obtained and were transplanted into greenhouse in September. The nursery plants were propagated in greenhouse in early September for further evaluation.10-E5-31 was initially selected for early maturity, high yield, and good flavor in 2016. In 2017, the seedlings from 10-E5-31 line were planted at Zhengzhou and Dengfeng for adaptability testing. The evaluation showed that this line had superb growing and fruiting performance in 2017. Three-year continual regional adaptability testing was conducted at Xinxiang ang Xinyang of Henan, Qinhangdao of Hebei, Wenshan of Yunnan from 2020 to 2023. It was named as Zhongmei Huayue in 2019 and was granted with certificate by the Ministry of Agricultural and Rural Affairs of the PRC in 2023. The average weight of the fruits was 24.9 g and the weight of the largest fruit was 62.9 g. The contents of soluble solids are 12.3%-15.7%. The fruit firmness is 2.47 kg·cm-2. The fruits were red or orange-red in color. The fruit quality was high with pleasant aroma was suitable for fresh eating. The fruits had good storage life. The plants had strong resistance to stresses, high propagation rate, and high yield. It could be cultivated in open field or in protected condition.